Methods for measuring venous peripherally inserted central catheters in newborns - Andreia Tomazoni; Patrícia Kuerten Rocha; Mavilde da Luz Gonçalves Pedreira; Elisa da Conceição Rodrigues; Bruna Figueiredo Manzo; Luciano Marques dos Santos (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the results of insertion procedures of Peripherally Inserted Central Catheters in newborns using two measurement methods. Methods: this is a randomized clinical trial, presenting descriptive and exploratory results of variables. It was held at a Neonatal Intensive Care Unit. Data were collected between September 2018 and 2019. The sample analyzed was 88 catheter insertion procedures, distributed in two groups. Study approved by an Institutional Review Board and obtained registration in the country and abroad. Descriptive analysis and logistic regression of data. Results: modified measurement obtained a significant difference for the central catheter tip location. Elective removals and adverse events were not significant between groups; however, poor positioning was related to adverse events. Conclusions: between the two methods analyzed, the modified measurement obtained better results in the proper catheter tip positioning and, consequently, less risk to patients.